Thermophoretic diagnosis of autoimmune diseases based on Escherichia coli with autodisplayed autoantigens - Lee, Ga-Yeon; Bong, Ji-Hong; Kim, Ji Yun; Yoo, Gu; Park, Min; Kang, Min-Jung; Jose, Joachim; Pyun, Jae-Chul (ELSEVIER SCIENCE BV, 2019)
The autoimmune diseases systemic lupus erythematosus (SLE) and Sjogren's syndrome (SS) are diagnosed by detection of autoantibodies against Ro and La protein autoantigens, respectively. In this work, the diagnosis of autoimmune diseases SLE and SS was demonstrated using thermophoresis of Escherichia coli with the autodisplayed autoantigens. Ro and La protein autoantigens were autodisplayed by constitutive expression together with a fluorescent protein called tdTomato in the cytosol. The binding affinity of the autodisplayed autoantigens was tested against positive and control sera by using FACS as a reference method. The factors influencing interactions between E. coli with autodisplayed autoantigens and autoantibodies in sera during thermophoresis were analyzed by measurement of cell surface charge and size before and after interaction. Finally, the thermophoretic diagnosis of autoimmune diseases SLE and SS was demonstrated using sera from patients afflicted with the respective diseases by estimating sensitivity and selectivity from ROC plots. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: QUARTZ-CRYSTAL MICROBALANCE; MICROSCALE THERMOPHORESIS; PROTEIN; ANTIBODIES; PROMOTER; DISPLAY; ASSAY